2013
DOI: 10.1038/srep01297
|View full text |Cite
|
Sign up to set email alerts
|

Switch Attention to Listen

Abstract: The aim of this research was to evaluate the ability to switch attention and selectively attend to relevant information in children (10–15 years) with persistent listening difficulties in noisy environments. A wide battery of clinical tests indicated that children with complaints of listening difficulties had otherwise normal hearing sensitivity and auditory processing skills. Here we show that these children are markedly slower to switch their attention compared to their age-matched peers. The results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…Children with reported listening problems in absence of a hearing loss (LP) often perform poorly on tests of auditory processing skills such as listening in noise (Cameron and Dillon, 2007;Dhamani et al, 2013) and processing spectral and/or temporal sequences (McArthur and Bishop, 2001;Sharma et al, 2009). It is often difficult to determine whether poor auditory performance reflects an auditory processing disorder (APD) or some other impairment that affects auditory encoding (Cacace and McFarland, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Children with reported listening problems in absence of a hearing loss (LP) often perform poorly on tests of auditory processing skills such as listening in noise (Cameron and Dillon, 2007;Dhamani et al, 2013) and processing spectral and/or temporal sequences (McArthur and Bishop, 2001;Sharma et al, 2009). It is often difficult to determine whether poor auditory performance reflects an auditory processing disorder (APD) or some other impairment that affects auditory encoding (Cacace and McFarland, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Outcome measures show significant correlations of similar degree with attention, AWM, and NV-IQ. There are also other aspects of attention that we did not measure; for example measures of divided attention, or measures of attention switching that may also have demonstrated a stronger contribution from attention to the AP tasks (Dhamani et al 2013). Similarly, there are also other forms of working memory that have not been assessed, such as working memory updating or inhibition that may have shown a different contribution of working memory to the AP tasks (St Clair-Thompson & Gathercole 2006).…”
mentioning
confidence: 95%
“…In a majority of listening situations involving multiple talkers and distractors, there is temporal overlap of different sources in different spatial locations. In our earlier study (Dhamani et al, 2013), we designed a psychophysical paradigm that revealed substantially longer attention reorientation time, which may be the basis for poor attention switching ability in children with listening difficulties in background noise. In our earlier study (Dhamani et al, 2013), we designed a psychophysical paradigm that revealed substantially longer attention reorientation time, which may be the basis for poor attention switching ability in children with listening difficulties in background noise.…”
mentioning
confidence: 99%